Socio-cognitive interactions, narration of historicity and conditions of ethnolinguistic heterogeneity: a case study (Mazatec, South Eastern Mexico) (Signifiances (Signifying), 2022)
Mazatec, an Oto-Manguean language of south-eastern Mexico, with strong dialectal diversity, is a fitting example to illustrate the dynamics of socio-cognitive interactions, the narration of historicity and the conditions of ethnolinguistic heterogeneity. The model chosen for its analysis is Robert Nicolaï's semiotic construction theory, which explores the conditions in which sociolinguistic data and artefacts create meaning, or emergence of meaning through sociolinguistic data and constructs. First, taking the results of an intercomprehension survey conducted in 23 localities by Paul Livingston Kirk, who also described the comparative phonology of Mazatec dialects, we created here an array of visualization artefacts. These allow us to explore one aspect of the layering of speaker competence, as a virtual dimension of the repertoire. Second, using discursive field data collected near Huautla de Jiménez, we analyze a fragment of a Mazatec mythical narrative, rich in indices of historicity, illustrating the Mazatec verbal art and the processes whereby meaning is created in the language, through face to face interaction. The analysis further highlights the deep prevalence of language heterogeneity, even within the idiolect of a "monolingual" subject.